Florence and Cottonwood River Valley - Michael Stubbs (Symphony in the Flint Hills, 2009)
The Symphony in the Flint Hills 2009 concert site is situated in the uplands, south of the Cottonwood River on the Doyle Creek Ranch. We are guests of local ranchers Judy and Randy Mills. Our hosts have arranged for us to experience another unique Flint Hills Tallgrass Prairie landscape. This year we are near the headwaters of Turkey Creek, a spring, fed stream that flows north to the Cottonwood.
Keywords: Symphony in the Flint Hills; Florence; art; Kansas City Symphony; site; location; farm; ranch; family; tradition; Kansas; settlers; pioneers; Mexico; community; town; rural; settlement